BUILDING THE INDEX OF RESILIENCE FOR ISLAMIC BANKING IN INDONESIA: A PRELIMINARY RESEARCH - Arumsari, Fanny; Wiranatakusuma, Dimas Bagus; Ahmad, Abu Umar Faruq (International Journal of Islamic Economics and Finance (IJIEF), 2018)
The 2007-2008 global financial crises had brought severe financial instability in financial institutions, and since then it became more complex and irreparable. Therefore, it has become inevitable to examine various tools that can monitor resilience of these financial institutions, especially the banking system that plays significant role in economic development of a country. Although Islamic banking operates in the same financial environment, its distinguishing features and fundamental differences demand different treatment in building resilience. The scope of existing literature of banking surveillance tools is either to some extent, mostly limited to banking sector in general, or  it is dominated by partial developments. Hence, there is a significant gap that lies in the literature to address the specificity of Islamic and conventional  banking surveillance tools analysis to build resilience that can contribute to reduce the span of financial instability in a country. This study seeks to explore to fill in this gap in Indonesian jurisdiction. The study finds that optimum resilience level of Shari`ah banking in Indonesia exists in specific range as a result of the contribution that is made by each and  every indicator. The study also attempts to find a way to trace some indicators that could effectively contribute to prevent the instability of Shari`ah compliant banking system in Indonesia.